Exploring Reasons for Doing Plagiarism among Indonesian EFL Undergraduate Students: A Confirmatory Factor Analysis - Fauziah Khairani Lubis; Anna Riana Suryanti Tambunan; Widya Andayani Widya Andayani; Ada Marie Mascarinas; Shouket Ahmad Tilwani (Jurnal Ilmu Pendidikan, 2024)
The rapidly escalating plagiarism rate among students in higher education has become a global academic concern. This quantitative study investigated the factors that led to student plagiarism. Eighty EFL university students from Indonesia participated in this investigation. The online questionnaire consisted of two sections: demographic information and a plagiarism perception scale, which included perspectives on plagiarism, the perceived significance of plagiarism, and contributing factors to students' plagiarism. The results disclosed a superficial understanding of the various forms of plagiarism. Personal, academic, and institutional factors contributed to plagiarism in the research. To reduce the prevalence of plagiarism in later phases, the results highlighted the need for practical policies and a cohesive framework to increase students' awareness at the onset. Course instructors should take the development of solid writing and referencing skills seriously, and the common leniency towards instances of plagiarism by undergraduate students must be replaced with a more severe attitude that encourages innovative and authentic research practice. To reduce plagiarism effectively, it is essential to enhance students’ understanding of its seriousness, provide robust academic support, and ensure that institutional policies are clear, consistent, and enforced.